Magnetohydrodynamics with nanofluids for heat transfer applications - Selimefendigil, Fatih; Öztop, Hakan Fehmi (CRC Press, 2017)
In this chapter, the use of nanofluids to heat transfer applications with a magnetic field is numerically studied. Two examples are presented that are representative for many thermal engineering problems. A partially heated cavity and lid-driven cavity filled with nanofluid under the effect of an inclined magnetic field were numerically studied. The finite element method was used to solve the governing equations of systems. The influence of the magnetic field strength and inclination angle for various nanoparticle concentrations on the fluid flow and heat transfer characteristics was investigated in detail for a range of pertinent parameters. The results are presented with streamlines, isotherms, and local and averaged Nusselt number distributions for a range of parameters. © 2017 by Taylor & Francis Group, LLC.